2015
DOI: 10.1002/cncr.29245
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Dysphagia Inventory and videofluorographic swallowing study as prognostic indicators of early survival outcomes in head and neck cancer

Abstract: BACKGROUND:The prognostic role of swallowing-related, pretreatment subjective and objective findings has not been investigated in detail. The authors evaluated the association between pretreatment MD Anderson Dysphagia Inventory (MDADI) or videofluorographic swallowing study (VFSS) results and standard outcomes, including early recurrence and survival, in patients with treatment-na€ ıve head and neck squamous cell carcinoma (HNSCC). METHODS: Patients with HNSCC (n 5 191) who received treatment at the authors' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The median value of the global assessment score of the MDADI was 74 in our current study patients.The same score was found in the HNC patient cohort that included all ages in our previous study [9]. Similarly, we found that an MDADI ,70 was related to a lower 2-year overall survival rate.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The median value of the global assessment score of the MDADI was 74 in our current study patients.The same score was found in the HNC patient cohort that included all ages in our previous study [9]. Similarly, we found that an MDADI ,70 was related to a lower 2-year overall survival rate.…”
Section: Discussionsupporting
confidence: 88%
“…Older HNC patients have a relatively higher incidence of coexisting pulmonary diseases or degenerative neuromuscular disorders that can aggravate treatment-related complications and may lead to insufficient treatment or even treatment discontinuation [6]. Importantly, HNC itself and its associated aerodigestive complications during patient follow-up can lead to early death and noncancerous demises [7][8][9]. Therefore, pretreatment evaluation of the functional age of geriatric HNC patients should include assessment of swallowing and respiration abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Larger sample sizes are needed to power hypotheses regarding differences between staging subgroups. Evidence of associations between age, T stage, and site of disease with long-term swallowing outcomes in OPC cohorts is reported by many investigators and supports need for prospective identification of patients at higher risk for poorer swallowing outcomes [3133]. …”
Section: Discussionmentioning
confidence: 95%
“…The deintensification regimens and dosimetric radiotherapy approaches designed to limit acute and chronic toxicity for patients with oropharyngeal cancer with biologically favorable tumor biology and with few dysphagia‐related symptoms at baseline may not benefit patients presenting with advanced disease and dysphagia before starting radiotherapy. Baseline patient‐reported dysphagia was shown to be an independent predictor of survival . Patients reporting dysphagia before radiation are also subject to chronic dysphagia after radiation, despite radiation dose reductions to swallowing structures .…”
Section: Introductionmentioning
confidence: 99%
“…Baseline patient-reported dysphagia was shown to be an independent predictor of survival. 3,4 Patients reporting dysphagia before radiation are also subject to chronic dysphagia after radiation, despite radiation dose reductions to swallowing structures. 2 Thus, patients with preexisting dysphagia are subject to both disability and death.…”
Section: Introductionmentioning
confidence: 99%